Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.33495/jerr_v7i10.19.149
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of research ability among nurses in a tertiary hospital in China: A cross-sectional survey

Abstract: The existing literature on research ability among clinical nurses in tertiary hospitals in well-developed areas in China is sparse. The aim of this study is to explore the level of research ability and its determinants among clinical nurses in China. A cross-sectional survey was conducted and a total of 627 registered clinical nurses were recruited and surveyed with the Scale of Nursing Scientific Research ability. T-test and One-way ANOVA were used in this study.Quantitative results showed that the mean score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Besides, those who had participated in academic conferences in the past 5 years, those who planned to improve their education in the next 5 years and those with a positive research attitude had stronger abilities for scientific research. Among them, continuing educational learning factors related to scientific research had a greater impact on the level of research competence, which was consistent with previous findings by Wang, Xie, et al (2019). These data, to some extent, affirm the significance of scientific research training in improving the research abilities of community nurses.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, those who had participated in academic conferences in the past 5 years, those who planned to improve their education in the next 5 years and those with a positive research attitude had stronger abilities for scientific research. Among them, continuing educational learning factors related to scientific research had a greater impact on the level of research competence, which was consistent with previous findings by Wang, Xie, et al (2019). These data, to some extent, affirm the significance of scientific research training in improving the research abilities of community nurses.…”
Section: Discussionsupporting
confidence: 91%
“…Relevant studies showed that the Cronbach's α coe cient of the total scale is 0.861 and the Cronbach's α coe cient of each dimension is 0.655~0.760. One month later, the correlation coe cient of the total scale of test-retest reliability is 0.902 (30). In our study, the Cronbach's coe cient of this scale before and after intervention was 0.946 and 0.973, respectively.…”
Section: Outcome Measuressupporting
confidence: 46%
“…However, their research training needs were relatively high 53.12(37.50, 75.00) (29). In our previous study, we found that 89.2% nurses had a weak research ability (30). Therefore, research training with content to tailored to individual characteristics and capacities should be provided for nurses.…”
Section: Introductionmentioning
confidence: 96%
“…The scale was a ve-point ordinal scale (0-4) with a maximum score of 120 points; a higher score represents a higher level of research ability [33]. Relevant studies show that the scale has good reliability [34]. In our study, the Cronbach's coe cient of research ability was 0.983.…”
Section: Outcome Measuresmentioning
confidence: 60%